Microencapsulation: A Review - JYOTHI SRI.S; A.SEETHADEVI; K.SURIA PRABHA; P.MUTHUPRASANNA; P.PAVITRA (International Journal of Pharma and Bio Sciences, 2012)
Microencapsulation is the process of surrounding or enveloping one substance within another substance on a very small scale, yielding capsules ranging from less than one micron to several hundred microns in size. The encapsulation efficiency of the microparticles or microsphere or microcapsule depends upon different factors like concentration of the polymer, solubility of polymer in solvent, rate of solvent removal, solubility of organic solvent in water etc. Microencapsulation may be achieved by a myriad of techniques. Substances may be microencapsulated with the intention that the core material be confined within capsule walls for a specific period of time. Alternatively, core materials may be encapsulated so that the core material will be released either gradually through the capsule walls, known as controlled release or diffusion, or when external conditions trigger the capsule walls to rupture, melt, or dissolve. This article is a review of microencapsulation and materials involved in it, morphology of microcapsules, microencapsulation technologies, purposes of microencapsulation, and benefits of microencapsulation, release mechanisms, and application fields, with special emphasis on microencapsulated additives in building construction materials